The antineoplastic effect of low-molecular-weight heparins – a literature review - Bochenek, Justyna; Püsküllüoğlu, Mirosława; Krzemieniecki, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2013)
There is some evidence for the antitumor effect of heparins, especially the low-molecular-weight ones. The authors discuss the potential mechanism of this antineoplastic effect and present results from several in vitro and in vivo experiments. The clinical trials concerning the impact of low-molecular-weight heparins on the tumor and on the patients’ survival are described. The objective was to find out if heparins could be administered as an antitumor drug, independently of their anticoagulatory properties. The antitumor role of tissue factor, heparinase, chemokines, stromal proteins, cellular interactions as well as angiogenesis and immunology seems certain. The results of the available studies seem promising but large clinical trials are necessary in order to confirm the antineoplastic effect of the low-molecular-weight heparins and to approve them for standard anticancer treatment. It could be a breakthrough in modern oncology.